The book and its history: first part - William Hernandez Ospino (Universidad del Magdalena, 2014)
The birth of the book goes back five thousand years. The ancient Egyptians, whose culture has influenced the West realized a plant with slender stem and several meters high which they called Papyrus. The stem of this plant drew the Egyptians several strips when dry, are arranged in parallel layers overlapping at the edges perpendicular adding to them another set of strips.